Exploring Students' Difficulties in Speaking English and Their Attitude In Speaking English - Inayah, Ratih; Lisdawati, Ida (LPPM Universitas Advent Indonesia, 2017)
The purpose of English language education is to provide students with the capabilities to understand the language in appropriate way and to have good ability in written and oral (Richard, 2008). If students are not able to speak English fluently and clearly, this purpose will be hard to achieve. So, it is essential to study this phenomenon in order to discover if students actually have problems with speaking, and then we can recognize what kind of problems and the reason of it also their perception in Speaking English as a foreign language in Indonesia. This study employed qualitative research paradigm as an intensive, holistic description, and analysis of a single instance, phenomenon, or social unit (Alwasilah, 2011). The study employed a descriptive method with multi instruments as observation, questionnaires, and interviews. Populations of this research were taken from a class of last semester students at STKIP Siliwangi Bandung and the sample were taken from four high achievers and four low achievers from the classroom. The result showed that students’ behavior lead them to speaking difficulties, those who are not interested in speaking activity, relatively get trouble in speaking for academic purposes. This study showed that students who experience difficulties with speaking often have problems with their motivation and self-confidence so that they feel quite hard to recognize their true skill. Somehow, many students have positive attitude and perception toward the concept of fluency in speaking English. They consider that fluency in speaking is something important to master; they think it will be very useful for their carrier in the future. Keywords : Speaking English, Difficulties